Groundwork for the Anthropology of Belgium: An Overlooked Microcosm of Europe. Issue 3 (26th May 2016) - Blainey, Marc G.
ABSTRACT: Like the European Union itself, the anthropology of Europe has been slowly developing for decades. Yet compared to their colleagues working at more conventional non-Western field sites, ethnographers studying present-day Europe are focusing on a region that still exists at the margins of the discipline. Thus far, anthropologists have largely neglected Belgium as an opportunity to understand the sociopolitical culture of the European continent as a whole. Through a detailed examination of historical processes that have shaped modern Belgian society, the present article highlights how this tiny nation stands as a microcosm of Europe's past, present, and potential futures. Proffering a wide-ranging analysis of the various regional and supranational spheres that Belgians inhabit, this paper outlines how ethnographic studies of belgitude (or 'Belgianness') can shed light on pan-European topics that are of interest to anthropologists.